Massive Open Online Courses (MOOCs) as instruments of soft power and public diplomacy (International relations and international law Journal, 2021)
A relatively new phenomenon, Massive Open Online Courses (MOOCs) officially entered our lives around 2008, and since then it has been gaining popularity all over the world. Audience growth, advances in technology, and globalization make MOOCs an important means of communication that can serve more than just educational purposes. In this paper, the author tries to position MOOCs within the concepts of soft power and public diplomacy and related sub-concepts. The article examines MOOCs as a channel of communication within public diplomacy and their practical functions for achieving humanitarian and political goals. The author describes several different scenarios of how MOOCs can function as a tool of public diplomacy, generating soft power for state and non-state actors who reach out to the foreign public. Thus, MOOCs can be used to teach a country’s history and culture, market the national higher education system, strengthen structural relations through language, reinforce structural relations through technology, stimulate the development of partner countries by providing access to education, and create networks for multilateral cooperation. The author concludes with a discussion of directions for further research.Key words: MOOC, soft power, public diplomacy, education diplomacy, digital diplomacy.